Tafsir Remaja di Indonesia: Analisis Kepengaran, Penyajian, dan Metodologi - Chalimah Abdullah; Nurul Istiqomah (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2025)
This article examines youth-oriented Qur’anic exegesis in Indonesia as a new segment within popular tafsir. It aims to analyze the characteristics of youth tafsir through three aspects: authorship, presentation, and exegetical methodology. The study employs qualitative library research using content analysis on three works explicitly addressed to young readers: Reflection on Surah Three Qul, Tafsir Gaul: Bebas Masalah Cara Al-Qur’an untuk Remaja, and Be Moslem Scientists. The findings show that youth tafsir in Indonesia is marked by the expansion of exegetical actors beyond formally trained Qur’anic studies scholars, while still deriving legitimacy from classical and contemporary tafsir sources. In terms of presentation, youth tafsir tends to employ popular language, thematic organization, visual elements, and communicative formats that resonate with young audiences. Methodologically, these works combine transmitted elements with ijtihādī-contextual approaches to connect Qur’anic messages with the experiences of young readers. Thus, youth tafsir may be understood as a mode of interpretation that rearticulates the tafsir tradition in a form more adaptive to the literacy culture of younger generations.